STRATEGY OF INFORMATION IMPLEMENTATION METHODOLOGY TECHNOLOGIES IN THE LEARNING PROCESS - N.O. Poberezhna (Academy of Cognitive and Natural Sciences, 2010)
In this article ways of readiness of the future teachers to use of competition technologies in education process are considered.